Industrial Relations Dispute Resolution Reform in Court: A Review of Structural and Substantial Weaknesses in Law Number 2 of 2004 - Justisi, Eigen; Safa’at , Rachmad; Koeswahyono , Imam; Djatmika , Prija (CV. AFDIFAL MAJU BERKAH, 2024)
Conflict resolution in the context of industrial relations within the framework of labor law after the enactment of Law Number 2 of 2004 concerning Industrial Relations Dispute Settlement has been known through two mechanisms, namely voluntary settlement through bipartite mechanisms, conciliation, mediation, and arbitration, as well as compulsory settlement mechanisms through the Industrial Relations Court. However, the existence of the Industrial Relations Court poses several challenges, including workers' low understanding of the formal and material aspects of labor law, protracted processes, and substantial deficiencies in applicable law. Issues that arise around the resolution of industrial relations disputes include various factors, ranging from disputes regarding rights, interests, termination of employment, to disputes between unions in a company. In addition, the limited competence of the Industrial Relations Court also hinders effective resolution of labor disputes. This research adopts a normative juridical approach, which relies on positive legal analysis, especially Law Number 2 of 2004, as well as a review of judicial principles. The research findings identified a number of weaknesses, both in terms of structure and legal substance, that require updates in Industrial Relations Dispute Resolution in the Industrial Relations Court. One of the efforts to overcome these challenges is through reforms in the settlement process at the Industrial Relations Court, including the establishment of Industrial Relations Courts in each administrative region. However, Law Number 2 of 2004 is still considered unable to accommodate judicial principles